2018
DOI: 10.1063/1.5042098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lattice curvature and crystalline homogeneity for 2-inch GaN homo-epitaxial layer

Abstract: We evaluated the lattice curvature, crystallinity, and crystalline homogeneity of a GaN layer on a free standing GaN substrate using lattice orientation measurements, θ rocking curves, and reciprocal space mapping from synchrotron X-ray diffraction topography, and X-ray diffraction. The lattice curvature of the 2-inch GaN homo-epitaxial layer was a concave bend, which had a curvature radius of approximately 20.7 m. The GaN layer was epitaxially grown on the GaN substrate and had good crystallinity with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…However, the values at the wafer edge are lower than those at the wafer center implying an azimuthal angle dependence of the bending of the wafer. According to Seo et al, 23 they showed homogeneous radii of curvature of 20.4 and 20.8 m at ϕ = 0 and 120°, which are smaller than our results (∼35 m), evaluated from the center of Fig. 4(a) and (c), but uniform due to the isotropic wafer bending.…”
Section: Experimental Details and Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…However, the values at the wafer edge are lower than those at the wafer center implying an azimuthal angle dependence of the bending of the wafer. According to Seo et al, 23 they showed homogeneous radii of curvature of 20.4 and 20.8 m at ϕ = 0 and 120°, which are smaller than our results (∼35 m), evaluated from the center of Fig. 4(a) and (c), but uniform due to the isotropic wafer bending.…”
Section: Experimental Details and Resultscontrasting
confidence: 90%
“…17 The radius of curvature evaluated from this value is about 50 m, which was larger than that in a previous report on a 2-inch GaN homo-epitaxy. 23…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…If the angular step of sample rotation is too high or the Bragg peak is too sharp, some parts miss the Bragg condition, which shows a zebra-like pattern after the merging of the diffracted images, even though the crystallinity is high. 37 To avoid this artefact, the size of the angular step can be decreased. Unlike at ϕ = 0°, the inclined diffraction peak was observed at ϕ = 120°.…”
Section: Methodsmentioning
confidence: 99%